PEMILIHAN KODE BAHASA DALAM RANAH PENDIDIKAN DAN KERJA: STUDI KASUS DI PUSAT BAHASA, BUDAYA, DAN AGAMA UIN SUNAN KALIJAGA - , ROSIANA KRISTANTI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Language choice in multilingual societies in the educational institution as in Center for language, Culture and Religion UIN Sunan Kalijaga (CLCRU) is an interesting phenomenon based on the sociolinguistics point of view. This research is aimed at describing the codes, code switching and code mixing, functions of code switching and code mixing and social factors of language choices in CLCRU. The research uses a descriptive qualitative research, particularly the Sociolinguistics approach. The data of the research are the lingual units in the form of words, phrases, or sentences in the speech events in CLCRU. The method in data collection uses recording technique, interview, interview, and documentation. The first finding of this research shows that the codes in the form of languages found in CLCRU are Indonesian (I), Arabics (A), English (E) and Javanese (J). Codes in form of styles can be divided into formal style, informal style, and slang style. Codes in the form of speech level can be divided into low Javanese speech level (ngoko) and high Javanese speech level (krama). The second finding is that code switching and code mixing found in CLCRU vary. Code-switching can be divided into (1) codeswitching from Arabic to Indonesian, (2) Arabic to English, (3) Arabic to Javanese, (4) English to Indonesian, (5) English to Javanese, and (6) Javanese to Indonesian. Meanwhile, code-mixing can be divided into code mixing in the forms of words, phrases, and clauses. The words-code mixing can use English, Arabic, Indonesian, and Javanese bases. The third finding shows that the functions of code switching are to clarify the materials in foreign language teaching, to build intimate situation in learning, to switch topics, to show certain group identities, to show solidarity expressions, to build intimacy and informal situation, to emphasize the message of utterances, and to show respect. In addition, the functions of code mixing cover to clarify materials in foreign language teaching, to be stylish, to talk certain topics, to show respect, to be the self-expression, to borrow particular terms, to clarify the addresseeâ intention, and to refer to certain things. The fourth finding reveals that factors of language choices include participants, addressee, situation, ends, topics, and norms of interaction. In detail, those factors are 1) participants: a) speakers consist of certain group membership, speakerâs aspiration, gender, age, and educational background, language proficiency of speaker, b) addressees, c) third speakers